EFEKTIVITAS ANTIBIOTIK PADA PASIEN PNEUMONIA COVID-19 : STUDI OBSERVASIONAL - Farid Zulkarnain Nur Syah; Abdul Rahem; Anita Purnamayanti; Rella Indah Karunia (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2022)
COVID-19 has become a deadly pandemic worldwide. The use of empiric antibiotics in cases of COVID-19 pneumonia has the risk of triggering bacterial resistance. The purpose of the study was to analyze the use of antibiotics used in cases of COVID-19 pneumonia. The design of the study was an observational study conducted retrospectively from June 2021 to August 2021. The subjects of the study were patients with confirmed COVID-19 pneumonia, as diagnosed by the doctor based on the results of a chest CT scan and PCR. The total number of research subjects was 111. The antibiotics used were azithromycin (n = 42) and levofloxacin (n = 69). There was no significant difference between the initial clinical condition of hospital admission in subjects receiving azithromycin and subjects receiving levofloxacin (p=0.098) based on the WHO clinical progression scale score. There was a significant difference between azithromycin and levofloxacin for the length of therapy (p = 0.000) and length of hospitalization (p = 0.004). There was a significant difference (p = 0.006) in clinical conditions based on WHO clinical progression scale scores before and after using azithromycin. There was no significant difference (p = 0.114) in clinical conditions before and after using levofloxacin. There was no significant difference in mortality (p = 0.275) between the two types of antibiotics. Subject mortality was not affected by gender, advanced age (> 65 years), and comorbid disease. Azithromycin is more effective in improving the clinical condition of patients with COVID-19 pneumonia compared to levofloxacin.